2012
DOI: 10.1371/journal.pone.0030589
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics Failure and Oxidative Stress in Brain Stem Mediates Cardiovascular Collapse Associated with Fatal Methamphetamine Intoxication

Abstract: BackgroundWhereas sudden death, most often associated with cardiovascular collapse, occurs in abusers of the psychostimulant methamphetamine (METH), the underlying mechanism is much less understood. The demonstration that successful resuscitation of an arrested heart depends on maintained functionality of the rostral ventrolateral medulla (RVLM), which is responsible for the maintenance of stable blood pressure, suggests that failure of brain stem cardiovascular regulation, rather than the heart, holds the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Complex II couples the oxidation of succinate to fumarate in the matrix with the reduction of ubiquinone in the membrane [19]. To assess complex II activity directly we measured the production of ubiquinol [15], which demonstrated that HFHS feeding caused a marked decrease in complex II activity. Complex II consists of four nuclear-encoded proteins - SDH subunits A, B, C and D. SDHA and SDHB are exposed to the matrix, while SDHC and SDHD are in the inner membrane [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex II couples the oxidation of succinate to fumarate in the matrix with the reduction of ubiquinone in the membrane [19]. To assess complex II activity directly we measured the production of ubiquinol [15], which demonstrated that HFHS feeding caused a marked decrease in complex II activity. Complex II consists of four nuclear-encoded proteins - SDH subunits A, B, C and D. SDHA and SDHB are exposed to the matrix, while SDHC and SDHD are in the inner membrane [20].…”
Section: Discussionmentioning
confidence: 99%
“…Complex II enzyme activity of isolated mitochondria was measured using microplate assay kit (Abcam/Mitosciences ab109908/MS241), as previously described [15]. In this assay kit, complex II is immunocaptured within the wells of the microplate.…”
Section: Methodsmentioning
confidence: 99%
“…Complex II enzyme activity of isolated mitochondria was measured using microplate assay kit (Abcam/Mitosciences ab109908/MS241), as previously described [20]. In this assay kit, complex II was immunocaptured within the wells of the microplate.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, under pathological conditions, our laboratory has demonstrated in comatose patients that irreversible loss of baroreflex-mediated sympathetic vasomotor tone is a hallmark for brain death12131415. We further identified that nitrosative stress in key nuclei of the neural circuit is the culprit for the defunct baroreflex16 in animal models of brain death16171819202122232425. Intriguingly, patients with alcoholic cirrhosis exhibit reduced baroreflex sensitivity26, and the degree of decreased HR variability is related to the severity of HE in patients with cirrhosis27.…”
mentioning
confidence: 91%